Excellence, equity and efficiency in educational psychology service delivery: a journey. Issue 4 (2nd October 2022) - Owen, Liz; Craig, Lesley; Barrett, Whitney; Hannay, Sam
ABSTRACT: Excellence, equity and efficiency are key drivers for improvement in Scotland's education sector, including educational psychology. This paper discusses and evaluates the decisions taken by one Scottish Educational Psychology Service towards achieving the key outcomes of excellence, equity and efficiency through a redesign of their service delivery model. Evidence is presented regarding the impact of this journey towards achieving these key outcomes, and reflections made about the mechanisms which facilitated this process of organisational change and service redesign.